2018
DOI: 10.1002/adma.201802025
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Functionalization of Wide‐Bandgap Dielectric Oxides by Boron Interstitial Doping

Abstract: A surge in interest of oxide-based materials is testimony for their potential utility in a wide array of device applications and offers a fascinating landscape for tuning the functional properties through a variety of physical and chemical parameters. In particular, selective electronic/defect doping has been demonstrated to be vital in tailoring novel functionalities, not existing in the bulk host oxides. Here, an extraordinary interstitial doping effect is demonstrated centered around a light element, boron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Versatile, but intriguing electronic and magnetic phenomena, such as two-dimensional high-mobility electron gas 1 , 2 , magnetoelectricity 3 , 4 , chiral magnetic domains 5 , 6 and topological phenomena 7 , 8 , have all been observed in various strongly correlated complex oxide systems with tunable magnetoelectric properties. These physical systems have significant potential in spin-based energy applications, such as low-energy consumption electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Versatile, but intriguing electronic and magnetic phenomena, such as two-dimensional high-mobility electron gas 1 , 2 , magnetoelectricity 3 , 4 , chiral magnetic domains 5 , 6 and topological phenomena 7 , 8 , have all been observed in various strongly correlated complex oxide systems with tunable magnetoelectric properties. These physical systems have significant potential in spin-based energy applications, such as low-energy consumption electronics.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates that, in addition to conventional techniques, an innovative combination of high-resolution 11 B solid-state magic-angle-spinning nuclear magnetic resonance spectroscopy (MAS NMR) and broadline 105 Pd solid-state static NMR, synchrotron X-ray powder diffraction (SXRD), aberration-corrected scanning transmission electron microscopy-annular dark-field (STEM-ADF) imaging, in situ X-ray pair distribution function (XPDF), electron energy loss spectroscopy (EELS), and electron ptychography can be used to characterize the Pd- int B/C NPs system. This industrial-type powder catalyst was chosen as a case study for the investigation of Pd host unit cell structural modification and B atom location.…”
Section: Introductionmentioning
confidence: 99%
“…In the upper 3D nanocomposite film layer, the two vertically aligned LAO and LBO structures are tightly coupled through the vertical interfaces. We found that the lattice match between LAO and LBO phases occur via aligning the LAO [29,30] Consequently, our results directly show that the consecutive formation of coherent 2D film layer and vertically arrayed 3D film is spontaneously formed in the LABO/STO(001) heterostructures (Figure 2g).…”
Section: Growth Mechanism Of Self-assembled 2d-3d Labo Nanocomposite ...mentioning
confidence: 65%